Needless Retesting of Quality-Assured, Commercially Prepared Culture Media - Nagel, Janice G. (1973)
Current revival of interest in quality control of bacteriological culture media prompted this laboratory to develop and implement a system of quality control testing of media purchased from commercial manufacturers. During 8 months we tested more than 900 lots of 46 different media representing 350,000 units of culture media purchased from two major and one minor supplier(s). Only 17 lots were found to be unsatisfactory. This experience raised a question about the real necessity for extensive retesting by users of commercially prepared, quality-assured media. It is suggested that primary responsibility for quality control be placed on the relatively few manufacturer-vendors rather than on the multiple purchaser-users, who may not possess either the expertise or the resources for quality control programs.